Umbilical cord blood DNA methylation in children who later develop type 1 diabetes - Laajala Essi; Kalim Ubaid U; Grönroos Toni; Rasool Omid; Halla-aho Viivi; Konki Mikko; Kattelus Roosa; Mykkänen Juha; Nurmio Mirja; Vähä-Mäkilä Mari; Kallionpää Henna; Lietzen Niina; et al. (SPRINGER, 2022)
Aims/hypothesis: Distinct DNA methylation patterns have recently been observed to precede type 1 diabetes in whole blood collected from young children. Our aim was to determine whether perinatal DNA methylation is associated with later progression to type 1 diabetes.
Methods: Reduced representation bisulphite sequencing (RRBS) analysis was performed on umbilical cord blood samples collected within the Finnish Type 1 Diabetes Prediction and Prevention (DIPP) Study. Children later diagnosed with type 1 diabetes and/or who tested positive for multiple islet autoantibodies (n = 43) were compared with control individuals (n = 79) who remained autoantibody-negative throughout the DIPP follow-up until 15 years of age. Potential confounding factors related to the pregnancy and the mother were included in the analysis.
Results: No differences in the umbilical cord blood methylation patterns were observed between the cases and controls at a false discovery rate <0.05.
Conclusions/interpretation: Based on our results, differences between children who progress to type 1 diabetes and those who remain healthy throughout childhood are not yet present in the perinatal DNA methylome. However, we cannot exclude the possibility that such differences would be found in a larger dataset.